How Ice Rink Locations Affect Performance Time in Short-Track Speed Skating - Sun, Lixin; Guo, Tianxiao; Liu, Fei; Tao, Kuan (Frontiers in Psychology, 2022)
Purpose: To accurately provide evaluations on how match performance for elite skaters in short track speed skating developed, geographical factors of ice rink locations should be considered apart from technical abilities. We created a dataset containing competition records from 2013-14 to 2020-21 seasons (500m event) on the official website. Methods: One-way ANOVA was applied to statistically analyze whether the best performance times exhibited significant differences in varied hosting cities. Performance-time matrix and multivariate regression model were further established to quantitatively explain how geographical factors (longitude, latitude, altitude and barometric pressure) affected performance. Results: Our findings firstly confirmed that the fastest 500m finishing times varied due to hosting cities (P-value = 0.008), and showed that venue locations could boost or impair performance time with the maximum range of 3.6 seconds. Meanwhile, latitude (slightly over 46 degrees when performance is maximized) was the most influential factor to account for performance-time difference in different ice rink locations according to the multivariate regression model, though altitude (1225 meters when performance is maximized) was also important. Conclusions: In this perspective, elite skaters should check the geographical factors of the venues before they participated in the upcoming competitions, assessed the real strength of their rivals and adopted flexible tactics during training sessions.